1999
DOI: 10.1210/jc.84.5.1617
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Chances to Conceive in Ovulatory Patients during Clomiphene Citrate Induction of Ovulation in Normogonadotropic Oligoamenorrheic Infertility

Abstract: The present prospective follow-up study was designed to identify whether clinical, endocrine, or ultrasound characteristics assessed by standardized initial screening of normogonadotropic oligo/amenorrheic infertile patients could predict conception in 160 women who reached ovulation after clomiphene citrate (CC) medication. Additional inclusion criteria were total motile sperm count of the partner above 1 million and a negative history for any tubal disease. Daily CC doses of 50 mg (increasing up to 150 mg in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 0 publications
4
69
1
1
Order By: Relevance
“…This is in accordance with previous observations (13,26). It has been suggested that the association of hypovitaminosis D with features of PCOS may be associated with obesity but not with the presence of PCOS (27).…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with previous observations (13,26). It has been suggested that the association of hypovitaminosis D with features of PCOS may be associated with obesity but not with the presence of PCOS (27).…”
Section: Discussionsupporting
confidence: 93%
“…Since LH determines the final stage of the oocyte nucleus maturation and the degeneration of gap junctions, the elevated levels of LH may also activate premature meiotic cleavage, damage the oocyte nucleus and lead to apoptosis [21]. High LH concentrations in patients with PCOS have been associated with an increased rate of miscarriage [22], although it has been questioned recently [23,24]. Increased androgen concentration in follicular fluid induced by elevated LH may block the dominant follicle selection and cause the follicle degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Sonographic monitoring was performed by a single observer (E v S), using an ultrasound machine (model EUB-415; Hitachi Medical Corp., Tokyo, Japan) with a 6.5 MHz transvaginal transducer. Endocrine screening included serum assays for FSH, luteinizing hormone, estradiol (E2), androstenedione, testosterone, sex-hormone binding globulin and insulin-like growth factor-I (IGF-I), as described previously (16). Hormone assays used and the intra-and inter-assay coefficients of variation for these assays have all been described previously (11,16).…”
Section: Subjects and Study Designmentioning
confidence: 99%